Sistem Informasi Pengelolaan Kegiatan Desa Dengan Desain UI&UX Sebagai Transparasi Di Desa Pertumbukan Kecamatan Wampu - Wijaya, Rian Farta; Fahmi Kurniawan; Putra, Randi Rian; Aldi Alvin (Universitas Sari Mutiara Indonesia Medan, 2024)
This research aims to develop and implement a village activity management information system with User Interface (UI) and User Experience (UX) design that focuses on transparency in Pertumbukan Village, Wampu District. This information system is designed to manage various village activities, including development planning, program implementation, and financial reporting, by providing easy and transparent access for the community. The UI&UX design used ensures that this system is intuitive and accessible to all levels of village society, including those who are less familiar with technology. The development of this system uses research and development (R&D) methods which involve the stages of needs analysis, design, development and system testing. The results of system testing show that this information system has succeeded in increasing the efficiency of managing village activities and strengthening the transparency and accountability of the village government to its citizens. Community participation in village activities has also increased, because the information conveyed through this system is easier to access and understand. The implementation of this information system in Pertumbukan Village has had a positive impact in the form of increasing community trust in the village government and speeding up the data-based decision making process.